2018
DOI: 10.1371/journal.pone.0209607
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, reliability, and validity of using accelerometers to measure physical activities of patients with stroke during inpatient rehabilitation

Abstract: Promoting physical activities is important for medical and functional recovery after stroke. Therefore, an accurate and convenient measurement of physical activities is necessary to provide feedback on functional status and effects of rehabilitative interventions. We assessed the feasibility, reliability, and validity of wearing accelerometers to monitor physical activities of stroke patients by estimating energy expenditure. This was a prospective observational quantitative study conducted in an inpatient reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previous investigations of adults with stroke have thus used wrist-worn accelerometers on both the affected and non-affected side (Schuiling et al, 2005; Bakken et al, 2011; Noorkõiv et al, 2014); however, these studies were not interested in PA, but rather sleep quality and upper limb movement. Recent work does indicate that wrist-worn accelerometers worn on either the stroke affected or non-affected side may be useful for examining PA of adults with acute stroke in an in-patient setting (Lee et al, 2018), but our study is the first to our knowledge which has examined the agreement and validity of wrist-worn accelerometers for measuring PA and SB among adults with chronic stroke.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous investigations of adults with stroke have thus used wrist-worn accelerometers on both the affected and non-affected side (Schuiling et al, 2005; Bakken et al, 2011; Noorkõiv et al, 2014); however, these studies were not interested in PA, but rather sleep quality and upper limb movement. Recent work does indicate that wrist-worn accelerometers worn on either the stroke affected or non-affected side may be useful for examining PA of adults with acute stroke in an in-patient setting (Lee et al, 2018), but our study is the first to our knowledge which has examined the agreement and validity of wrist-worn accelerometers for measuring PA and SB among adults with chronic stroke.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is important that a measure have evidence of validity and reliability for the population which one intends to observe (Falck et al, 2015). Wrist-worn actigraphy has potential as a tool for measuring PA and SB in adults with stroke (Lee et al, 2018), however adults with stroke expend more energy during walking than their healthy peers (Kramer et al, 2016). It is thus plausible that not only does the MW8 require a different calibration for adults with stroke, but that the side of the body which the MW8 is worn, and the severity of stroke require different calibrations of the device.…”
Section: Introductionmentioning
confidence: 99%
“…reaching or grasping) or non-task-specific arm-hand movement may limit the interpretation of results regarding any qualitative aspect of arm-hand motor behavior [30]. Wrist accelerometry is a valid and reliable measurement method [20, 31]. However, it measures ‘use’ and not ‘purposeful use’[73], and does not provide information about movement quality or specific activities that were performed during the wearing period.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that the monitoring of patients' mobility in an inpatient setting can give information similar to advanced and time-consuming techniques, such as behavioral mapping, and it can be useful to collect the activity levels of hospitalized patients [31]. A lower level of activity during hospitalization can lead to a loss of muscle quantity and quality and can seriously hurt the rehabilitation process and patient's health conditions [32][33][34]. A review on wearable sensors for the quantification of, and feedback on, lower extremity movement found that there may be substantial clinical benefits, with more work needed with respect to natural environments and longer monitoring periods [35].…”
Section: Introductionmentioning
confidence: 99%